Anti-Yo Positive Paraneoplastic Cerebellar Degeneration Unmasking Occult Right Breast Malignancy: A Case Report (Indian Journal of Case Reports, 2026)
Paraneoplastic cerebellar degeneration (PCD) is a rare autoimmune neurological syndrome associated with breast carcinoma and anti-Yo antibodies. Neurological symptoms often precede the diagnosis of the underlying malignancy. A 48-year-old woman presented with progressive swaying while walking for three months, slurred speech for two months, vomiting, and diplopia. She had a prior transient episode of acute cerebellar ataxia that improved after intravenous methylprednisolone. Examination revealed truncal and gait ataxia, gaze-evoked nystagmus, scanning speech, dysdiadochokinesia, and a firm right retroareolar breast lump. MRI brain showed blooming in the bilateral dentate nuclei and crus cerebri, likely due to mineral deposition. Mammography and ultrasonography revealed suspicious bilateral breast nodules and a suspicious right axillary lymph node. Core biopsy of the right breast lesion showed features suspicious for malignancy (B4). Anti-PCA-1/anti-Yo antibody was positive. The case highlights the importance of considering paraneoplastic syndromes in patients with unexplained progressive cerebellar dysfunction and the role of multimodality imaging in detecting occult breast malignancy.